Hubungan Antara Volume Oksigen Maximum (Vo2max) Dengan Kualitas Hidup Pada Lanjut Usia - SEFTIKA DEWI, ASRI; , Sugiono, Sst. FT, MH. Kes (2016)
Background: elderly is closely related to the physical and biological changes that occur. Physical and biological changes in the elderly is characterized by the occurrence of biological deterioration seen as symptoms of physical setbacks, including the cardiovascular system, the respiratory system, the musculoskeletal system, gastrointestinal system, integument system, neurological system, endocrine system and sistem sensory. In accordance with the explanation of the cardiovascular system became one of the changes that occur. Cardiovascular capacity reduction will lead to decreased VO2max it will affect the development of other body systems. Thus indirectly affect the quality of life on elderly. Objective: To determine the relationship between the maximum volume of oxygen (VO2max) with the quality of life on elderly. Methods: observational study design with cross sectional analytic study aims to determine the relationship between the maximum volume of oxygen with the quality of life on elderly, with a sample size of 82 people. Data were analyzed using univariate with frequency distribution table and bivariate test using chi-square test. Results: The relationship between the maximum volume of oxygen to the quality of life of the elderly. the results obtained (p = 0.206), so nothing a significant relationship between the two variables Conclusions: There was no relationship between the maximum volume of oxygen to the quality of life on elderly.